2008
DOI: 10.1016/j.stem.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Sall4 Regulates Distinct Transcription Circuitries in Different Blastocyst-Derived Stem Cell Lineages

Abstract: Stem cells self-renew or differentiate under the governance of a stem-cell-specific transcriptional program, with each transcription factor orchestrating the activities of a particular set of genes. Here we demonstrate that a single transcription factor is able to regulate distinct core circuitries in two different blastocyst-derived stem cell lines, embryonic stem cells (ESCs) and extraembryonic endoderm (XEN) cells. The transcription factor Sall4 is required for early embryonic development and for ESC plurip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
209
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(227 citation statements)
references
References 42 publications
17
209
1
Order By: Relevance
“…In stem cells, SALL4 functions as both an activator and a repressor of gene transcription depending on the cell context. It suppresses important differentiation genes and activates key pluripotency genes (Elling et al, 2006;Lim et al, 2008). It acts by regulating critical transcription factors and epigenetic modulators to activate or repress different transcriptional networks in self-renewal and pluripotency in ESCs, probably by recognizing specific DNA binding sites (Lim et al, 2008;Lu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In stem cells, SALL4 functions as both an activator and a repressor of gene transcription depending on the cell context. It suppresses important differentiation genes and activates key pluripotency genes (Elling et al, 2006;Lim et al, 2008). It acts by regulating critical transcription factors and epigenetic modulators to activate or repress different transcriptional networks in self-renewal and pluripotency in ESCs, probably by recognizing specific DNA binding sites (Lim et al, 2008;Lu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Having direct interaction with key cell-signaling pathways such as Wnt and TGF-beta, SALL4 can play essential roles in cell fate decision and survival of ESCs Shuai et al, 2009). SALL4 is an important regulator of the stemness state and survival, not only in several types of normal stem cells but also in cancer cells and possibly cancer stem cells (Lim et al, 2008). In adults, SALL4 expression is normally restricted to CD34+ hematopoietic stem/ progenitor cells , and in adult mice, SALL4 is also predominantly expressed in testes and ovaries (Kohlhase et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…20 Through physical and/or functional interaction with OCT4, SOX2, and NANOG, SALL4 plays an essential role in maintaining pluripotency and self-renewal of embryonic stem cells and hematopoietic stem cells. 4,5,19,21,22 SALL4 positively regulates OCT4 gene expression through binding to the conserved regulatory region of the OCT4 promoter. 5,11 On the other hand, SALL4…”
Section: Introducitonmentioning
confidence: 99%
“…The role of ILF2 during development is unclear, though interestingly it is associated with active chromatin in numerous embryonic tissues [82] and is known to interact with OCT4 and NANOG proteins in mouse ESCs [83]. Global transcriptome analysis of the embryo in the context of Oct4, Sall4 and Nanog depletion have revealed that these factors act as combinatorial regulators of developmentally important genes at preimplantation stages [84], including pluripotency factors such as Klf5 and Klf2, the epigenetic modifiers Dnmt3a and Dnmt3b, and the signalling molecules Fgf2, Fzd4 and Fzd7, as well as miRNAs with enhancers occupied by OCT4, SALL4 or NANOG in ESCs [85,86]. These data suggest that a feedforward loop consisting of pluripotency factors, miRNAs, Rbl2 and Dnmt3b regulates DNA methylation in the developing embryo and buffers fluctuations in the expression of regulatory genes that might otherwise disrupt normal cell fate specification [84].…”
Section: Regulatory Network For Pluripotency and Lineage Commitment mentioning
confidence: 99%